Pollination networks from natural and anthropogenic-novel communities show high structural similarity - Timóteo, Sérgio (2018)
The Anthropocene is marked by an unprecedented homogenisation of the world's biota, confronting species that never co-occurred during their evolutionary histories. Interactions established in these novel communities may affect ecosystem functioning; however, most research has focused on the impacts of a minority of aggressive invasive species, while changes inflicted by a less conspicuous majority of non-invasive alien species on community structure are still poorly understood. This information is critical to guide conservation strategies, and instrumental to advance ecological theory, particularly to understand how non-native species integrate in recipient communities and affect the interactions of native species. We evaluated how the structure of 50 published pollination networks changes with the proportion of alien plant species and found that network structure is largely unaffected. Although some communities were heavily invaded, the proportion of alien plant species was relatively low (mean = 10%; max. = 38%). We further characterized the pollination network in a botanic garden with a plant community dominated by non-invasive alien species (85%). We show that the structure of this novel community is also not markedly different from native-dominated communities. Plant-pollinator interactions revealed no obvious differences regarding plant origin (native vs. alien) or the native bioregion of the introduced plants. This overall similarity between native and alien plants is likely driven by the contrasting patterns of invasive plants (promoting generalism), and non-invasive aliens, suggested here to promote specialization.